Characterization of phytoconstituents, in vitro antioxidant activity and pharmacological investigation of the root extract of typhonium trilobatum - Shafa, Fahim (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2015.